Automated DNA sequencing and analysis - Adams, Mark D.; Fields, Chris; Venter, J. Craig (Academic Press, 1994)
A timely book for DNA researchers, Automated DNA Sequencing and Analysis reviews and assesses the state of the art of automated DNA sequence analysis-from the construction of clone libraries to the developmentof laboratory and community databases. It presents the methodologies and strategies of automated DNA sequence analysis in a way that allows them to be compared and contrasted. By taking a broad view of the process of automated sequence analysis, the present volume bridges the gap between the protocols supplied with instrument and reaction kits and the finalized data presented in the research literature. It will be an invaluable aid to both small laboratories that are interested in taking maximum advantageof automated sequence resources and to groups pursuing large-scale cDNA and genomic sequencing projects. * The field of automation in DAN sequencing and analysis is rapidly moving. Hovever, as the technology becomes commonplace, those applying the techniques involved to their research fields need a text which both expands on the protocols supplied by manufacturers with their instruments and explains how to utilise the data produced. This book fulfils those needs, reviews the history of the art and provides pointers to future development.